Information security - Zelkowitz, Marvin V., 1945- (Amsterdam ; San Diego, CA : Elsevier Academic Press, 2004)
The series covers new developments in computer technology. Most chapters present an overview of a current subfield within computers, with many citations, and often include new developments in the field by the authors of the individual chapters. Topics include hardware, software, theoretical underpinnings of computing, and novel applications of computers. This current volume emphasizes information security issues and includes topics like certifying computer professionals, non-invasive attacks ("cognitive hacking"), computer files as legal evidence ("computer forensics") and the use of processors on plastic ("smartcards"). The book series is a valuable addition to university courses that emphasize the topics under discussion in that particular volume as well as belonging on the bookshelf of industrial practitioners who need to implement many of the technologies that are described. In-depth surveys and tutorials on new computer technology Well-known authors and researchers in the field Extensive bibliographies with most chapters Five out of seven chapters focus on security issues Discussion of computer forensics, professional certification and smart cards A chapter on how DNA sequencing is accomplished is important in the growing bioinformatics field.
Licensing and certification of software professionals / Donald J. Bagert -- Cognitive hacking / George Cybenki, Annarita Giani, and Paul Thompson -- Digital detective : an introduction to digital forensics / Warren Harrison -- Survivability : synergizing security and reliability / Crispin Cowan -- Smart cards / Katherine M. Shelfer, Chris Corum, J. Drew Procaccino, and Joseph Didier -- Shotgun sequence assembly / Mihai Pop -- Advances in large vocabulary continuous speech recognition / Geoffrey Zweig and Michael Picheny.
Includes bibliographical references and indexes.
Keywords: Internet -- Security measures; Information technology -- Security measures; Electronic books